Development of a model to assess coastal ecosystem health using oysters as the indicator species. (5th February 2020) - Ahn, Jeong Eun; Ronan, Anne Dudek
Abstract: This work presents a new model that uses output from a three-dimensional (3-D) hydrodynamic simulation, rather than directly measured water quality variables, to determine zones where oysters can potentially survive, grow, and reproduce. The zones are delineated based on water depth, speed, salinity, temperature and vertical mixing. Vertical mixing, quantified by Richardson number, is used as a surrogate measure of replenishment of dissolved oxygen and food. The model has the benefit that it can be used in a predictive mode because of its reliance on 3-D hydrodynamic simulation results in the absence of water quality data. Therefore, it can be useful as a screening tool for oyster planting and restoration efforts that are occurring worldwide. The spatial extents of the zones can also provide a measure of coastal ecosystem health. Highlights: Model delineates zones that can benefit from oysters' ecosystem engineering ability. Criteria based on 3D hydrodynamic model output and no water quality model. Richardson number used as a surrogate for food and oxygen availability. Useful to predict impacts of altered hydrodynamics on ecosystem health. Also useful to aid oyster planting efforts.